Doubt's Boots Even Doubt's Shadow - Noble, Charles (Open Spaces, 2003)
Charles Noble's long poem playfully connects autobiography, narrative, philosophy, history, and satire and experiments with language and structure in a way that pushes the limits of contemporary poetry. Noble leaves no leaf unturned as he touches on issues related to contemporary Western society, including mass media culture, gender politics, postindustrial technology, and the politics of postmodern culture.